2019
DOI: 10.3389/fonc.2019.00784
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Rare Urethral Metastasis From Primary Lung Adenocarcinoma: Case Report and Literature Review

Abstract: Background: Lung adenocarcinoma is a common respiratory malignancy, however urethral metastasis of lung adenocarcinoma has not yet been reported. This study aims to present a rare case of isolated urethral metastasis in a male patient with a history of primary lung adenocarcinoma. Case Presentation: A 69 year-old male patient was admitted complaining of dysuria and nocturia for 3 months, with a history of lung adenocarcinoma after surgery. The patient was diagnosed as benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The most common site of metastasis is the small intestine, with isolated cases of large intestine and anus also reported (14). Since lung cancer progresses to intestinal metastasis without apparent symptoms, most cases are detected by examination to exclude common site metastasis (15). It is found that a small percentage of intestinal obstruction is due to intestinal metastasis (16).…”
Section: Discussionmentioning
confidence: 99%
“…The most common site of metastasis is the small intestine, with isolated cases of large intestine and anus also reported (14). Since lung cancer progresses to intestinal metastasis without apparent symptoms, most cases are detected by examination to exclude common site metastasis (15). It is found that a small percentage of intestinal obstruction is due to intestinal metastasis (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although various therapeutic approaches have been introduced for LUAD, there were still no obvious improvements in ameliorating unfavorable prognoses, especially in patients with metastatic disease. Metastases of LUAD to the nervous system, bone, liver, adrenal gland and even urethra tend to indicate poor therapeutic outcomes, and only some selected cases may benefit from systematic therapy [6][7][8]. The TNM staging system provides a relatively reliable predictive model for prognosis and remains the most frequently applied predictor of survival [9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on urethral metastasis is limited to case reports and a few small case series, with most publications focusing on histopathologic and clinical presentations rather than MRI findings. The scant reports of urethral metastasis have described spread from primary cancers such as colonic adenocarcinoma [6][7][8], prostate adenocarcinoma [9], melanoma [10], high grade ovarian serous cell carcinoma [11], renal clear cell carcinoma [12], and primary lung adenocarcinoma [13], among others [14]. In women, the most common locations of urethral metastasis involved either the external meatus or the whole urethra [1,5,6,8,10,15,16].…”
Section: Introductionmentioning
confidence: 99%